1984
DOI: 10.1128/jvi.49.2.426-436.1984
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of guinea pig cytomegalovirus DNA

Abstract: The genome of guinea pig cytomegalovirus (GPCMV) was analyzed and compared with that of human cytomegalovirus (HCMV). GPCMV and HCMV DNAs were isolated from virions and further purified by CsCl centrifugation. Purified GPCMV DNA sedimented as a single peak in a neutral sucrose gradient and was infectious when transfected into guinea pig embryo fibroblast cells. The cytopathology was characteristic of that seen after infection with GPCMV. Virus DNA purified from virions isolated from infected GPEF or 104C1 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…Slides were baked overnight at 56°C before in situ hybridization was performed. Biotinylated GPCMV DNA probes and a control pBR322 probe were prepared as described previously (6,16,24). The map location of each GPCMV probe on the GPCMV genome has been published (24).…”
Section: Methodsmentioning
confidence: 99%
“…Slides were baked overnight at 56°C before in situ hybridization was performed. Biotinylated GPCMV DNA probes and a control pBR322 probe were prepared as described previously (6,16,24). The map location of each GPCMV probe on the GPCMV genome has been published (24).…”
Section: Methodsmentioning
confidence: 99%
“…With regard to the presence of two populations of DNA molecules, therefore, RCMV is similar to GPCMV (Fig. 1) (158,230). A restriction endonuclease map of DNA obtained from an English strain of RCMV suggested that the overall genomic structure of both the English and the Dutch strains was very similar, although the English strain of RCMV has a smaller genome (206 kbp) (56).…”
Section: Molecular Biologymentioning
confidence: 99%
“…GPCMV DNA is a linear double-stranded molecule that has a buoyant density of 1.712 g/cm3, which corresponds to a G+C content of 54.1%, and is 239 kbp in length (107,158). Based on the hybridization of radiolabeled cloned or gelisolated GPCMV DNA fragments to Southern blot transfers of restriction enzyme-digested genomic GPCMV DNA, several restriction enzyme maps for the GPCMV DNA have been deduced (107).…”
Section: Replication and Biologymentioning
confidence: 99%
“…Antibodies to neutralizing epitopes on this protein block viral attachment to cell surfaces, viral penetration and cell to cell transmission, and viralinduced cell fusion [Navarro et al, 19931. DNA homology exists within the many common regions of the genomes of HCMV and gpCMV and within the region encoding for the gB protein there is 42% homology at the amino acid level [Isom et al, 1984;Schleiss, 19941. In spite of their biological similarities, their DNA sequence homologies, and the relatedness of their gB proteins, the antigenic relatedness of gpCMV and HCMV has not yet been fully investigated.…”
Section: Introductionmentioning
confidence: 99%